Pengaruh Return On Asset dan Debt To Asset Ratio Terhadap Harga Saham pada PT. Duta Pertiwi, Tbk - Ainul, Ainul; M. Rimawan; Puji Muniarty (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine: (1) the partial effect of Return on Assets (ROA) on stock prices of PT Duta Pertiwi Tbk, (2) the partial effect of Debt to Asset Ratio (DAR) on stock prices of PT Duta Pertiwi Tbk, and (3) the simultaneous effect of ROA and DAR on stock prices of PT Duta Pertiwi Tbk. This research employed an associative quantitative approach using secondary data derived from income statements and balance sheets, including net profit, total assets, total liabilities, and stock prices from 2014 to 2023. Data were collected through documentation and literature study, and analyzed using classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), multiple linear regression, correlation and determination coefficients, as well as t-test and F-test. The results indicate that: (1) ROA has no significant partial effect on stock prices, (2) DAR has no significant partial effect on stock prices, and (3) ROA and DAR jointly have no significant effect on stock prices of PT Duta Pertiwi Tbk.